Double-blind switch study of vilazodone in the treatment of major depressive disorder. (May 2017) - Grant, Jon E.; Redden, Sarah A.; Leppink, Eric W.
Abstract : Approximately 40% of patients treated for depression do not respond to a trial of an antidepressant. The aim of the proposed study was to evaluate the efficacy and safety of switching to vilazodone in patients with major depressive disorder who are unresponsive or only partially responsive to a trial of citalopram. Seventy-nine adults with major depressive disorder were enrolled in an open-label study of citalopram (20 mg/day) for 6 weeks. Those still symptomatic after 6-weeks of citalopram were randomly assigned to either a higher dose of citalopram (40 mg/day) or to vilazodone in a double-blind trial for 6 weeks. Of those who received citalopram 20 mg/day for 6 weeks, 20.3% were 'responders' (defined as ≥50% reduction on the Montgomery–Åsberg Depression Rating Scale). Of the 42 who did not respond, 23 were assigned to citalopram 40 mg/day and 19 were randomized to 40 mg/day of vilazodone. Both groups showed decreases in all outcome measures, but there were no significant differences between groups. Initial nonresponders to a low dose of citalopram seem equally likely to respond to a higher dose of citalopram or to vilazodone. Whether to increase an selective serotonin reuptake inhibitor or switch to a different antidepressant may be best determined on the basis of their adverse event profile.